Model Pembelajaran Inovatif pada Pelajaran Pendidikan Agama Islam - Munzillah, Indiarti Muafiqoh; Budiyono, Slamet (Lembaga Yasin AlSys, 2024)
Education is one of the sources of learning that can add knowledge and insight for each individual. A teacher in carrying out learning activities needs innovation in terms of learning methods, strategies, and others. So, students' learning activities do not feel bored. Learning that uses only one method can make students feel bored. So teachers need to provide some variation in the learning model given to students. The purpose of this study is 1) to find out the various innovative learning models, 2) to find out the advantages and disadvantages of each learning model, and 3) to find out examples of the implementation of each learning model. This study uses a qualitative research method with a literature model. The stages in analyzing data are doing it by reducing data, presenting data, and drawing conclusions. The researcher reduced the literature on the learning model, then presented it systematically. The final stage is to draw conclusions from critical analysis. The results of this research are that there are four innovative learning models, namely cooperative, contextual, problem-based, and project-based.